Feasibility and Preliminary Efficacy of a Novel RDoC-Based Treatment Program for Adolescent Depression: “Training for Awareness Resilience and Action” (TARA)—A Pilot Study - Henje Blom, Eva; Tymofiyeva, Olga; Chesney, Margaret A.; Ho, Tiffany C.; Moran, Patricia; Connolly, Colm G.; Duncan, Larissa G.; Baldini, Lisa; Weng, Helen Y.; Acree, Michael; Goldman, Veronica; Hecht, Frederick M.; et al. (Frontiers in Psychiatry, 2017)
Background The novel group treatment program Training for Awareness, Resilience, and Action (TARA) was developed to target specific mechanisms based on neuroscience findings in adolescent depression and framed within the NIMH Research Domain Criteria (RDoC). TARA contains training of autonomic and emotional self-regulation, interoceptive awareness, relational skills and values-based committed action. Methods We performed a single-arm trial to test the feasibility and preliminary efficacy of TARA in reducing depression and anxiety levels, and assessed whether the specific targeted domains of function reflected the hypothesized symptom change. Twenty-six adolescents (14-18 years old, 7 males and 19 females) participated in the 12-week group program. Assessment was performed before (T0), immediately after (T1) and three months after the end of TARA (T2). Results Significant improvement was seen in depression symptoms (Reynolds Adolescent Depression Scale, 2nd edition) between T0-T1 (t value = -3.56, p = 0.002, CI = (-6.64,-1.77)) and T0-T2 (t value= -4.17, p < 0.001, CI = -11.20, -3.75)) and anxiety symptoms (Multidimensional Anxiety Scale for Children) between T0-T1 (t value = -2.26, p = 0.033, CI=-4.61,-0.21) and T0-T2 (t value = -3.06, p = 0.006, CI95% (-9.02,-1.73). Significant improvements in psychological flexibility, sleep, and mindfulness skills were also found between T0-T2. Limitations The sample size was small without a control condition. The pilot design did not allow for testing the hypothesized brain changes, and effect of TARA on relevant systemic biomarkers. Conclusions TARA is feasible in a sample of clinically depressed and/or anxious adolescents and preliminary efficacy was demonstrated by reduced depression and anxiety symptoms. The specific symptom and behavioral outcomes corresponded well with the hypothesized mechanisms of change.